Keperluan Ijtihad dalam Pengurusan Pewarisan Harta: Kajian Terhadap Amalan Nuzriah di Singapura (Sains Humanika, 2012)
This article analyzes the need for ijtihad in the management of inheritance with particular reference to the practices on nuzriah in Singapore. For that purpose, the discussion has been made on a nuzriah case that was decided in the High Court of Singapore. In order to analyze the position of nuzriah, the authors has examined the legal views of fiqh, the contemporary fatwas, the provisions of law, and the objectives of Shariah in nuzriah implementation nuzriah in inheritance. The study found that nuzriah is an instrument for the distribution of property that is suitable to be practiced in certain situations to address issues of conflict in the inheritance. In the Singapore context, the concept of nuzriah can be adapted in planning the family property distribution in addition to the use of hibah, wills and trusts. Nevertheless, the effectiveness of nuzriah as estate planning instrument also depends on its compliance with both Civil law and Islamic law.
Keywords: Ijtihad; inheritance; nazar; nuzriah; Islamic Law in Singapore